MILITARY EDUCATION: A REFLECTION OF THE MODERN MAINSTREAM - Uvarkina, Оlena (Continuing Professional Education: Theory and Practice, 2022)
This article examines current problems of transformation of the system of military education, which require reflexion of basic and new conceptual constructs. The goal of the research is to identify the essence and specific features of the transformation of the military education system to the standards of the leading educational systems. In order to achieve the set goal, the methodological basis of the research was determined at the level of philosophical and general scientific positions: systematization, analysis, synthesis, extrapolation and simplification. The use of the method of structural-system analysis allowed us to identify the main trends of changes in the structure of the system of military education on the basis of best practices of the countries -. members of the Pan-Atlantic alliance. The essence of the immanence of leadership as the basis of professionalism of the military was revealed with the help of the cause-and-effect relations. the result of the consequential methodology of identifying functional and instrumental peculiarities and tendencies. As a result of the research, it was determined that the modern educational space, in the conditions of new trials, directs the system of military education to the implementation of new methods and forms of organization and management of military training. The systemic study of the conceptual framework of the military education system revealed new categorical structures and models in the processes of military transformation. It is noted that the introduction of professional military education into the structure of the military education system must solve the problem of professionalization and leadership in the military team. Particular importance is given to the value-motivational aspects of shaping the personality of the military man, which determines the motivation of the person to change and become a sign of his maturity as a person and a professional.